Principals’ Fund Management Strategies and School Administrative Effectiveness - Olaifa, Adeseko Sunday; Ajala, Sodiq; Olaifa, Ebunlomo Oreoluwa; Medupin, Abiodun Johnson; Adeoye, Moses Adeleke (Universitas Pendidikan Ganesha, 2024)
A lack of prudence and mismanagement of school funds by the principals could give rise to poor student performance since it might slow down the acquisition of essential materials for teaching and learning. This study analyzes the relationship between principals’ fund management strategies and school administrative effectiveness. It assessed principals' budgetary practices, the perceived level of administrative effectiveness, and the relationship between fund management on secondary schools' effectiveness. Two research questions and one hypothesis were generated for the study. The research design was the descriptive survey type. The population of the study comprised all the one hundred and thirty-two (132) secondary schools. The total number of respondents included forty (40) principals representing 30% of the population, who were selected using the stratified random sampling technique. A self-designed questionnaire titled